BRO RASTA CAKE: INOVASI BERAS HITAM KAYA MANFAAT SEBAGAI UPAYA PENINGKATAN KESEJAHTERAAN PETANI PADI HITAM DI DESA KALIGIRI - Tria Widi Pangestika; Anik Ma’ruf Al Kahfi; Dema Javi Lorensya; Tuva Yulia Purnamasari (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2018)
Kaligiri village is a village with a prosperous agricultural potential one of which is its black rice, but most local farmers have not been able to develop innovation due to minimal education and knowledge. With the entrepreneurship training and product making of BRO RASTA CAKE it is hoped that farmers can learn about new innovations of processed black rice to improve their economy, BRO RAST CAKE training includes entrepreneurship training, product marketing training and black rice Brownies making practices, which are interdependent from all three training. The result is that farmers are able to make innovations of processed food products from black rice that can boost their economy and also create new jobs. Implementation of Community Empowerment Community Creativity Program (PKMM) entitled BRO RASTA CAKE: Black Rice Innovation Rich Benefit as Efforts to Improve the Welfare of Black Rice Farmers in Kaligiri Village Sirampog Sub District as an effort to increase the income of farmers community Kaligiri Village Sirampog District Brebes Regency has been running smoothly and reach Output target